A First dictionary of cultural literacy : what our children need to know - Hirsch E D 1928; Rowland William G; Stanford Michael 1923 (Boston : Houghton Mifflin, 1989)
Presents an outline of the knowledge that, according to the Cultural Literacy Foundation, should be acquired by the end of sixth grade, in such categories as literature, religion and philosophy, history, geography, mathematics, science, and technology.
Includes index.
Bibliography: p. 249-254.
Keywords: Civilization -- Dictionaries Juvenile; English language -- Dictionaries, Juvenile; Encyclopedias and dictionaries; United States -- Civilization -- Dictionaries Juvenile